Development of Nurse Role Model in Improving Patient Safety - Halawa, Afeus; Setiawan, Setiawan; Syam, Bustami (Jurnal Keperawatan Soedirman, 2021)
ABSTRACTPatient safety has become a global issue of concern in health care. Various efforts have been made to improve patient safety in the hospital by involving the health team, one of which is a nurse, a health worker who interacts 24 hours with patients. The role of nurses is a major factor in improving patient safety in the hospital. The purpose of this study was to develop a role model for implementing nurses in improving patient safety at Rumah Sakit Umum Deli Medan. This research was a qualitative research with an action research approach involving 15 nurses as participants. Data collection was carried out by means of focus group discussions (FGD), observation, and questionnaires about the role in patient safety. The data obtained were evaluated using content analysis and simple statistics. The results of this study were in the form of a blueprint for the role model of the implementing nurse in improving patient safety, with the outcome of the increasing knowledge of the implementing nurse. The researchers concluded that proper implementation was very important to raise awareness of the importance of preventing incidents of injury to patients. Keywords: Role, Nurse, Patient Safety